Personalized medicine in allergic asthma: at the crossroads of allergen immunotherapy and “biologicals” - Fritzsching, Benedikt (Frontiers in Pediatrics, 2017)
Major allergic disease can be viewed as clinical syndromes rather than discrete disease entities. Emerging evidence indicates that allergic asthma includes several disease phenotypes. Immunological deviation towards high T helper cell type 2 (Th2) cytokine levels has been demonstrated for a subgroup of pediatric asthma patients and now several novel monoclonal antibodies have been approved for treatment of this subgroup as a stratified approach of "personalized" medicine in allergy. Introduction of component-based IgE testing before allergen immunotherapy (AIT), i.e. testing for IgE-crossreactivity before initiation of AIT, has also brought stratified medicine into allergy therapy. Improved responder criteria, which identify treatment-responders previous to therapy, might foster this stratification and even individualized AIT might have an impact for tailor-made therapy in the future. Furthermore, combining antibody-based treatment with AIT could help to establish more rapid AIT protocols even for allergens with a high risk of anaphylactic reactions. Efforts to advance such "personalized" medicine in pediatric allergy might be challenged by several issues including: High costs for the healthcare system, increasing complexity of allergy therapy, the need for physician allergy expertise and furthermore ethical considerations and data safety issues.
Gesehen am 24.05.2018